Oral Fluoroquinolones in the Treatment of Pneumonia, Bronchitis and Sinusitis - Nicole Mittmann; Farah Jivraj; Angelina Wong; Alice Yoon (Canadian Journal of Infectious Diseases)
BACKGROUND: Despite a relatively large number of clinical studies comparing oral fluoroquinolones to one antibiotic class comparator, there is limited information on the relative efficacy of different fluoroquinolones.